2016
DOI: 10.1155/2016/4609784
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Electroacupuncture Pretreatment on Myocardial Ischemia/Reperfusion Injury via Antiapoptotic Signaling

Abstract: Objectives. Our previous study has used RNA-seq technology to show that apoptotic molecules were involved in the myocardial protection of electroacupuncture pretreatment (EAP) on the ischemia/reperfusion (I/R) animal model. Therefore, this study was designed to investigate how EAP protects myocardium against myocardial I/R injury through antiapoptotic mechanism. Methods. By using rats with myocardial I/R, we ligated the left anterior descending artery (LAD) for 30 minutes followed by 4 hr of reperfusion after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 60 publications
5
31
0
Order By: Relevance
“…Interestingly, miR-214 is considered as a target for treatment of I/R diseases due to its protective roles in I/R disease. For instance, the nonselective β-adrenergic receptor antagonist carvedilol or electroacupuncture pretreatment enhanced cardiac function and inhibited cardiomyocyte damage upon simulate I/R injury via enhancing miR-214 expression [8,17]. In the present study, overexpression of miR-214-5p was able to reduce the cardiac cell damage and apoptosis induced by I/R injury in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, miR-214 is considered as a target for treatment of I/R diseases due to its protective roles in I/R disease. For instance, the nonselective β-adrenergic receptor antagonist carvedilol or electroacupuncture pretreatment enhanced cardiac function and inhibited cardiomyocyte damage upon simulate I/R injury via enhancing miR-214 expression [8,17]. In the present study, overexpression of miR-214-5p was able to reduce the cardiac cell damage and apoptosis induced by I/R injury in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 54%
“…Patients who have undergone cardiac surgery have shown signi cantly improved heart rates, blood pressure, and rates of recovery after receiving EA stimulation [29]. Recently, researchers found that EA pre-treatment improved the survival rate of rats with myocardial ischemia-reperfusion injury with reduced apoptosis and expressions of Cyt c and cleaved caspase 3 [30,31]. EA regulated the activation of NLRP3, polarization of macrophages, declined arrhythmia scores, improving cardiac function [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers found that EA pre-treatment improved the survival rate of rats with myocardial ischemia-reperfusion injury with reduced apoptosis and expressions of Cyt c and cleaved caspase 3 [30,31]. EA regulated the activation of NLRP3, polarization of macrophages, declined arrhythmia scores, improving cardiac function [18,31]. EA played a role of antiarrhythmia through reducing ventricular tachycardia and ventricular, and related to concentration of calcium in the cytoplasm [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg1 upregulates the expression of eNOS by targeting miR-214, which is beneficial for promoting angiogenesis [68]. Electroacupuncture preconditioning can upregulate the expression of miR-214 and inhibit the increase in Ca 2+ , sodium/calcium exchanger 1 (NCX1), BCL2-like 11 (BIM), calmodulin-dependent protein kinase IIδ (CaMKIIδ), cyclophilin D (CypD), and other related proteins that have accumulated in hypoxia injury in H9c2 myocardial cells, and play a protective role in ischemia/reperfusion (I/R) [69]. e Fuzheng Huayu capsule has the effect of alleviating myocardial fibrosis after MI in rats.…”
Section: Circrna-mirna-mrna In Chdmentioning
confidence: 99%